Adaptive dual-mode OFDM with index modulation - Aldırmaz Çolak, Sultan; Başar, Ertuğrul; ACAR, YUSUF (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2018)
With the integration of the index modulation concept, the popular OFDM has gained an appealing new dimension. However, OFDM with index modulation (OFDM-IM) causes a decrease in data rate for higher order modulations due to its unused subcarriers. Recently, dual-mode OFDM with index modulation (DM-OFDM-IM) has been proposed to prevent this decrease in data rate. The spectral efficiency (SE) of both techniques depends on the selection of different parameters, such as modulation types and number of active subcarriers. However, the quality of the wireless channel has not been taken into account yet to increase the data rate. In this paper, we propose a new adaptive DM-OFDM-IM (A-DM-OFDM-IM) system to enhance the bit error probability (BER) performance considering the channel conditions and obtain a substantial increase in SE. Unlike the previous DM-OFDM-IM and the classical OFDM-IM schemes, our proposed system enables the use of different types of modulations for different subblocks in one OFDM signal. We demonstrate that the SE of the proposed system is comparable with that of its OFDM-IM and DM-OFDM-IM counterpart under frequency selective Rayleigh channels. Moreover, computer simulations corroborate that the derived theoretical results are considerably accurate for the SE of A-DM-OFDM-IM systems. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: OFDM-IM; Dual mode OFDM-IM; Adaptive-OFDM; Spectral efficiency